Exploration of pro-apoptotic effect of Thymoquinone on oral squamous cell carcinoma cells through PI3K/Akt signaling pathway - Ren, Xun; Luo, Wei (Cellular and Molecular Biology, 2019)
Oral squamous cell carcinoma (OSCC) is the sixth most prevalent cancer type in the world, with a 5-year survival rate of only 40% to 50%. Finding effective anti-tumor drug candidates is quite necessary for the progression of OSCC therapy. In this study, the role of Thymoquinone (TQ) in OSCC cells was studied. It was confirmed that TQ can inhibit the proliferation, migration and invasion of KB cells, and can also achieve apoptosis by inhibiting the activation of PI3K/Akt pathway. Therefore, TQ is an effective candidate for the treatment of OSCC.